Pohon Hayat Nusantara dalam Perspektif Semiotika: Analisis Semiotika Roland Barthes terhadap Logo IKN - Faisal Muzzamil (UPT Publikasi Ilmiah UNISBA, 2025)
Pohon Hayat Nusantara by Aulia Akbar was selected as the winner in the competition for the Logo of the Indonesian Capital City (IKN) in East Kalimantan. This research on Pohon Hayat Nusantara in a Semiotic Perspective is based on Roland Barthes' Semiological Elements theory. Based on the aforementioned theory, there are two main objectives in this research, namely: First, to reveal the denotative meaning of Pohon Hayat Nusantara as the IKN Logo; Second, to reveal the connotative meaning of Pohon Hayat Nusantara as the IKN Logo. This research uses a semiotic analysis method based on Roland Barthes' semiological elements theory. Based on the results of the semiotic analysis of Pohon Hayat Nusantara as the IKN Logo, two analysis results and research findings were obtained, namely: First, Pohon Hayat Nusantara has four denotative meanings, namely (1) Pohon Hayat Nusantara brings a new spirit to start a new life with the new National Capital; (2) The Indonesian Tree of Life symbolizes the natural wealth of Indonesia in the form of forests, seas, rivers and its archipelago; (3) The Indonesian Tree of Life instills the values of nationalism in all Indonesian people; (4) The Indonesian Tree of Life represents the cultural diversity of the Indonesian people and nation. Second, the Indonesian Tree of Life has three connotative meanings, namely: (1) The meaning of life, symbolized by the Kalpataru Tree; (2) The meaning of security, symbolized by the Talawang Shield; (3) The meaning of culture, symbolized by the Pallawa script.